The evolution of UN sanctions : from a tool of warfare to a tool of peace, security and human rights /: from a tool of warfare to a tool of peace, security and human rights. ([2017]) - Carisch, Enrico; Rickard-Martin, Loraine; Meister, Shawna R
No abstract available